2015
DOI: 10.1038/jhh.2015.1
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure and arterial stiffness in patients with high sodium intake in relation to sodium handling and left ventricular diastolic dysfunction status

Abstract: In a population with high sodium consumption, we assessed relation between brachial and central blood pressures, elastic properties of large arteries, echocardiographic left ventricular diastolic function and sodium reabsorption as fractional urinary lithium excretion in proximal (FELi) and fractional sodium reabsorption in distal tubules assessed using the endogenous lithium clearance. Mean±s.d. age of 131 treated hypertensive patients (66 men and 65 women) was 61.9±7.5 years. We found significant interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…For increased salt intake to result in permanent changes in arterial pressure, renal function must be altered [25]. An increase in salt intake would lead to an increase in blood pressure and vice-versa, increased sodium reabsorption in the proximal tubule, and damage to the vascular wall as documented in previous studies [22, 26, 27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For increased salt intake to result in permanent changes in arterial pressure, renal function must be altered [25]. An increase in salt intake would lead to an increase in blood pressure and vice-versa, increased sodium reabsorption in the proximal tubule, and damage to the vascular wall as documented in previous studies [22, 26, 27].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this hypothesis, diminished capacity for sodium and water excretion has been observed in models of hypertension. In those who develop hypertension, the blood pressure does not return to normal, possibly due to vascular damage and diastolic dysfunction [26]. Chronic but mild hypervolemia and hypertension could be the long-term consequences of reduced sodium excretion [29], and this may explain the comparatively higher systolic blood pressure in normotensive patients with positive family history of hypertension who are at a higher risk of developing high blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…First, patients with OH have a higher risk of heart failure with preserved ejection fraction compared with patients without OH (HR, 1.32; 95% CI, 1.07–1.48; P =.033) . Second, Cwynar and colleagues found that hypertension patients with diastolic LV dysfunction have near‐significantly higher values of CSBP than patients without diastolic LV dysfunction (135.1±20.3 mm Hg vs 127.3±19.7 mm Hg, P =.049). Third, Borlaug and colleagues showed that LV diastolic and systolic tissue velocities vary inversely with arterial afterload, with late systolic load having the greatest influence on early diastolic velocity.…”
Section: Discussionmentioning
confidence: 99%
“…The study design has been described in detail elsewhere. 14 Briefly, all patients were requested to complete a standard epidemiologic questionnaire including detailed medical history, antihypertensive medications, and socioeconomic and demographic characteristics. The patients provided written informed consent to participate in the study.…”
Section: Methodsmentioning
confidence: 99%